233Conventional fluoroscopy guided vs zero-fluoroscopy catheter ablation of supraventricular tachycardias. (18th June 2020) - Prolic Kalinsek, T; Pernat, A; Jan, M; Sorli, J; Vrbajnscak, M; Sinkovec, M; Antolic, B; Klemen, L
Abstract: Funding Acknowledgements: None Introduction Conventionally, catheter movement and placement during catheter ablation (CA) is guided by X-ray fluoroscopy. In recent years, an 'as low as reasonably possible' principle was established to minimize the ionizing radiation dose received by the patient and the operator. Zero-fluoroscopy approach is at the extreme end of the spectrum of this principle. With exclusion of X-ray fluoroscopy, three-dimensional electroanatomical mapping system and intracardiac echocardiography are used for catheter guidance during ablation procedures. Purpose: The aim of our study was to assess and compare procedural parameters and clinical outcomes of conventional X-ray fluoroscopy guided and zero-fluoroscopy CA for treatment of supraventricular tachycardias. Methods: Retrospective analysis included CA procedure between April 2014 and May 2019. Five hundred and thirteen (513) patients were selected for analysis; they had confirmed diagnosis of atrioventricular nodal reentry tachycardia (AVNRT) or atrioventricular reentry tachycardia (AVRT). Patients were divided into two groups based on the use of fluoroscopy (conventional approach group - CG; zero-fluoroscopy group - ZF). Procedural data and clinical outcomes were analyzed. Two groups were compared using chi-squared test or Mann-Whithney U test when appropriate. Results: There were 249 patients (44.2% males) in CG group, and 260 patients (47.5% males) in ZF group. ZF group included 113 (43.5%) pediatric patients. The groups differed in mean age (53.4 ± 16.4 years vs 30.0 ± 19.8 years (CG vs ZF), p < 0.001), postprocedural use of antiarrhythmic agents or beta blockers (55.3% vs 17.0% (CG vs ZF), p < 0.001) and type of arrhythmia (72.3% vs 60.6% AVNRT (CG vs ZF), p = 0.003). In CG group, all procedures were performed using radiofrequency (RF) energy, whereas in ZF group, cryoablation was used in 18.3% of procedures at the discretion of the operator. Mean procedural duration was longer in CG group (100.1 ± 48.8 vs 90.4 ± 83.0 minutes, p < 0.001). The mean fluroscopy time was 13.6 ± 9.3 minutes and mean dose area product was 554.1 ± 713.6 mGycm2 in the CG group. Acute success rate was higher in CG group (95.7 vs 90.7%, p = 0.027). However, the arrhythmia-free survival rate after 13.8 ± 11.0 months of follow-up was lower in the CG group (90.9 vs 96.5%, p = 0.009). Mean number of procedures per patient was 1.04 in the CG group and 1.14 in the ZF group (p < 0.001). There were no severe complications. Conclusions: Zero-fluoroscopy CA of supraventricular tachycardias is associated with lower procedural success rate, but higher long-term arrhythmia-free survival rate when compared to conventional fluoroscopy guided procedures. It is possible, that these differences are stemming from somewhat different patient populations in both groups.